Anti-hyperglycemic contours of Madhugrit are robustly translated in the Caenorhabditis elegans model of lipid accumulation by regulating oxidative stress and inflammatory response - Balkrishna, Acharya; Gohel, Vivek; Pathak, Nishit; Tomer, Meenu; Rawat, Malini; Dev, Rishabh; Varshney, Anurag (Frontiers in Endocrinology, 2022)
Background: The prevalence of diabetes has considerably increased in recent years. In the long run, use of dual therapy of anti-diabetic agents becomes mandatory to attain euglycemia. Also, the incidences of diabetes-related co-morbidities have warranted the search for new therapeutic approaches for the management of the disease. Traditional herbo-mineral, anti-diabetic agents like Madhugrit are often prescribed to mitigate diabetes and related complications. The present study aimed to thoroughly characterize the pharmacological applications of Madhugrit. Methods: Phytometabolite characterization of Madhugrit was performed by high performance liquid chromatography. Evaluation of cell viability, α-amylase inhibition, glucose uptake, inflammation, and wound healing was performed by in vitro model systems using AR42J, L6, THP1, HaCaT cells, and reporter cell lines namely NF-κB, TNF-α, and IL-1β. The formation of advanced glycation end products was determined by cell-free assay. In addition, the therapeutic potential of Madhugrit was also analyzed in the in vivo Caenorhabditis elegans model system. Parameters like brood size, % curling, glucose and triglyceride accumulation, lipid deposition, ROS generation, and lipid peroxidation were determined under hyperglycemic conditions induced by the addition of supraphysiological glucose levels. Results: Madhugrit treatment significantly reduced the α-amylase release, enhanced glucose uptake, decreased AGEs formation, reduced conversion of monocyte to macrophage, lowered the pro-inflammatory cytokine release, and enhanced wound healing in the in vitro hyperglycemic (glucose; 25 mM) conditions. In C. elegans stimulated with 100 mM glucose, Madhugrit (30 µg/ml) treatment normalized brood size, reduced curling behavior, decreased accumulation of glucose, triglycerides, and lowered oxidative stress. Conclusions: Madhugrit showed multimodal approaches in combating hyperglycemia and related complications due to the presence of anti-diabetic, anti-inflammatory, anti-oxidant, wound healing, and lipid-lowering phytoconstituents in its arsenal. The study warrants the translational use of Madhugrit as an effective anti-diabetic medicine.